Morar en la memoria (2023)
Through this monograph, the project Morar en la memoria is presented, it is the writing that shows how the visual artist assumes ways of practicing formal languages ​​and allows them to be expanded by crossing those limits between two-dimensionality and three-dimensionality. It shows the development of a proposal where the painting expands through the installation of the constituencies of the contextualized object, the aim is to provide experiences in so-perceptu which allows the memory to be detonated through the activation of the senses.